Farmers' perception, knowledge and practices towards decline in production of large cardamom in Sankhuwasabha district of Nepal: Decline in production of large cardamom in Nepal - Gotame, Mahima; Santosh, B K (Journal of Spices and Aromatic Crops, 2025)
Large cardamom (Amomum subulatum) is a vital crop and a symbol of national identity in Nepal, particularly serving as a primary source of livelihood for farmers in the eastern hill regions. In recent years, however, a noticeable decline in cardamom productivity has posed serious challenges to major growing districts. This study aims to assess farmers’ perceptions, knowledge, and management practices related to large cardamom decline in Sankhuwasabha district. A total of 84 cardamom farmers were selected using a simple random sampling technique for an in-person household survey. The results indicate that 72.6% of respondents are experiencing severe crop decline, with many plantations in critical condition. The issue has persisted for over five years. Most farmers attributed the decline primarily to pest and diseases. Alarmingly, 89.3% of growers anticipated complete orchard collapse within the next 2–3 years if the situation remains unaddressed. While farmers expressed frustration over the ineffectiveness of past interventions, 70.2% remained hopeful that improved management practices could reverse the trend. The decline has significantly affected 67.9% of orchards, though some have shown slower rates of deterioration. Notably, 76% of farmers lacked adequate awareness regarding the causes and control measures for the decline. Approximately 60% continue to follow traditional cultivation practices, with most relying on mechanical and cultural methods for disease and pest management. Limited technical knowledge and poor access to agricultural inputs were identified as major constraints to the adoption of effective management strategies.